PENGARUH STRATEGI BISNIS DAN KETIDAKPASTIAN LINGKUNGAN TERHADAP KINERJA USAHA - Jhosefine, Octalivia; Holiawati, Holiawati (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2024)
This research was conducted with the aim of analyzing the influence of business strategy and environmental uncertainty. This research was conducted by analyzing business performance in MSMEs in Cibodas District, Tangerang City. This type of research is quantitative and associative using primary data in the form of distributing questionnaires to MSME business actors. Sampling used the slovin  sampling technique with the results of 88 MSME business actors. The variables used in this study are Business Strategy as the first independent variable and Environmental Uncertainty as the second independent variable and Business Performance as a bound variable. This study uses multiple linear regression analysis tests and hypothesis testing using the help of SPSS 25 software. The results of this study state that business strategy and environmental uncertainty simultaneously and partially affect business performance